L’adaptation aux risques d’inondation façonnée par les métiers de la ville - Mathilde Gralepois; Sofia Guevara (Développement Durable et Territoires)
This article shows how adaptation policy for flood risk is shaped by the local public procurement’s ambivalent position regarding urban development projects in flood area. Instead of using it as an opportunity to renew urban planning, adaptation policy overemphasizes the presence of water in order to justify the increase of building projects. In addition, adaptation policy is shaped by competition between urban planning professionals. These are forced to reposition themselves either by diversifying their skills or by seeking to hyperspecialize within urban project dynamics. Three profiles are studied. Water engineers translate controversial regulation rules into urban shapes. Restrained by these rules, architects protect their esthetical role but have to work with landscape designers, who transform the symbolic value of spaces generated by flood risk zones regulation.